TEACHING ENGLISH THROUGH LITERARY WORKS - Achmad Basari (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2007)
To be successful in teaching English as a Foreign Language needs various methods and approaches. One of the methods that can be an alternative is using literary works, such as drama, prose and poetry. They can be valuable resources to teach the language aspects such as vocabularies, pronunciation, and grammar. It can also be used as an effective way to create an engineered real-life situation for learners to practice the language. And in the long run, such a way of teaching English will also create appreciation and enjoyment for the learners.